2021
DOI: 10.1192/j.eurpsy.2021.2258
|View full text |Cite
|
Sign up to set email alerts
|

Risks of all-cause death and completed suicide in patients with schizophrenia/schizoaffective disorder treated with long-acting injectable or oral antipsychotics: A population-based retrospective cohort study in Taiwan

Abstract: Background: Long-acting injectable (LAI) antipsychotics improve medication adherence in patients with schizophrenia and provide an extended duration of therapeutic drug levels but with administration of an increased dose. Real-world mortality data in patients prescribed LAIs are lacking. We conducted a population-based cohort study to estimate and compare the incidence rates of all-cause death and completed suicide in patients with schizophrenia/schizoaffective disorder exposed to LAIs and oral antipsychotics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Relative to aripiprazole, quetiapine increased the 3-year mortality risk, a result that is consistent with some (Katona et al, 2014;Tang et al, 2022) but not all (Taipale et al, 2020;Tiihonen & Taipale, 2019) existing evidence. Although confirmatory research is needed, our findings suggest caution in the use of quetiapine in the care of non-elderly adults with SMI, even when used in low doses, as some evidence exists of the drug's risks at low dose (Berge, Abri, Andell, Movahed, & Ragazan, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Relative to aripiprazole, quetiapine increased the 3-year mortality risk, a result that is consistent with some (Katona et al, 2014;Tang et al, 2022) but not all (Taipale et al, 2020;Tiihonen & Taipale, 2019) existing evidence. Although confirmatory research is needed, our findings suggest caution in the use of quetiapine in the care of non-elderly adults with SMI, even when used in low doses, as some evidence exists of the drug's risks at low dose (Berge, Abri, Andell, Movahed, & Ragazan, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…While two studies compared SGAs or FGAs to no antipsychotic (Taipale et al, 2020 ; Tiihonen & Taipale, 2019 ), a third compared antipsychotic monotherapy to antipsychotic polypharmacy (Katona, Czobor, & Bitter, 2014 ). We are aware of only one recently published study that conducted pairwise comparisons between multiple antipsychotic drugs and oral paliperidone (Tang et al, 2022 ), and of one study among adults with treatment-resistant MDD that compared augmentation with a SGA to a second antidepressant (Gerhard et al, 2020 ). Across these studies conducted in SMI cohorts, aripiprazole appeared among the safest, with haloperidol's risk comparatively higher.…”
Section: Introductionmentioning
confidence: 99%
“…We further found that in the present study, PP1M treatment was not associated with a higher risk of serious and life-threatening cardiovascular events (HR 0.86) compared with oral SGAs. Few studies have previously examined the risk associations between LAI antipsychotic treatment and serious cardiovascular events, although meta-analyses and real-world studies suggested that use of LAIs was not associated with elevated risks of all-cause death, sudden death or cardiovascular death, or was associated with lower mortality compared with oral antipsychotics [ 42 , 48 , 49 ]. Furthermore, the null risk associations for expanded serious cardiovascular events (HR 0.88) reflected no elevated risks for a larger set of serious cardiovascular events associated with PP1M treatment, and such evidence can be used to enrich cardiovascular risk profiles for PP1M.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample consisted of inpatients with a short duration of schizophrenia. Then, the evidence of LAI antipsychotics and subsequent suicides has been rare [ 30 ].…”
Section: Discussionmentioning
confidence: 99%